2011
DOI: 10.13005/bpj/254
|View full text |Cite
|
Sign up to set email alerts
|

Hypertensive and Sympathomimetic Effects of the Methanol and Aqueous Extracts of Scoparia dulcis in Anaesthetized Male Wistar Rats

Abstract: Objective Scoparia dulcis, a widely used medicinal plant is believed to have antihypertensive effects among traditional medical healers. This study investigates the efficacy of Scoparia dulcis as an antihypertensive agent in Wister rats. Methods Plant specimens were collected from local gardens in Portharcourt and identified in Department of plant Science, University of Portharcourt. Methanol and aqueous extracts were made from the leaves of the plant. Phytochemical screening was done using conventional method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 5 publications
(5 reference statements)
0
6
0
Order By: Relevance
“…Review of Freire et al in 1993, Chow et al in 1974and Esume et al 2011 found that dose dependent hypertension produced by the ethanolic extract of S. dulcis and its aqueous fraction is useful for treatment of hypertension. 66,88,91 However, low-dose norepinephrine and epinephrine are easily degraded in the digestive tract aer oral administration and are not absorbed into the blood in signicant amounts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Review of Freire et al in 1993, Chow et al in 1974and Esume et al 2011 found that dose dependent hypertension produced by the ethanolic extract of S. dulcis and its aqueous fraction is useful for treatment of hypertension. 66,88,91 However, low-dose norepinephrine and epinephrine are easily degraded in the digestive tract aer oral administration and are not absorbed into the blood in signicant amounts.…”
Section: Discussionmentioning
confidence: 99%
“…Review of Freire et al in 1993, Chow et al in 1974and Esume et al 2011 found that dose dependent hypertension produced by the ethanolic extract of S. dulcis and its aqueous fraction is useful for treatment of hypertension. 66,88,91 However, low-dose norepinephrine and epinephrine are easily degraded in the digestive tract aer oral administration and are not absorbed into the blood in signicant amounts. Nevertheless, the test results of Esume et al 2011 88 also display that the higher doses of the aqueous and methanol extract of S. dulcis leaves signicantly increased blood pressure, heart rate and mean arterial pressure.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It is a perennial herb widely distributed in tropical and sub-tropical regions. In these regions, fresh or dried S. dulcis plants have been traditionally used as remedies for various ailments such as stomach problems that is, peptic ulcer,[ 9 ] hypertension,[ 10 ] hyperlipidemia,[ 11 ] hepatic injury,[ 12 ] algesia, and inflammation. [ 13 14 ] It has various biologically active secondary metabolites such as carbohydrates, coumarins, phenols, saponins, glycosides, tannins, amino acids, flavonoids, terpenoids, catecholamine, noradrenaline, and adrenaline.…”
Section: Introductionmentioning
confidence: 99%